Leukocyte telomere length, mitochondrial DNA copy number, and coronary artery disease risk and severity: A two-stage case-control study of 3064 Chinese subjects - Wang, Xue-bin; Cui, Ning-hua; Zhang, Shuai; Liu, Ze-jin; Ma, Jun-fen; Ming, Liang (Atherosclerosis, 2019)
Leukocyte telomere length (TL) and mitochondrial DNA copy number (mtDNA-CN), as hallmarks of cellular aging, may be involved in the development of coronary artery disease (CAD) by modulating oxidative stress. This study aimed to investigate the effects of leukocyte TL and mtDNA-CN alone or in combination on CAD risk and severity in the Chinese population. In this two-stage case-control study with 1511 CAD patients and 1553 controls, leukocyte TL and mtDNA-CN were determined by a quantitative PCR assay. Three oxidative parameters, including leukocyte 8-hydroxy-2′-deoxyguanosine (8-OHdG), plasma malondialdehyde, and plasma reactive oxygen species (ROS), were quantified by ELISA or colorimetric kits in a subset of 129 cases and 129 controls. In the combined cohort, each 1-SD decrease in TL and mtDNA-CN was significantly associated with a 1.17-fold and 1.14-fold increased risk of CAD (p < 0.001 for all), respectively, after adjusting for confounders. The aggregated score, which reflected the cumulative dosage of the tertiles of TL and mtDNA-CN, showed inverse dose-response correlations with CAD risk (ptrend < 0.001), and severity, as determined by the severity of clinical presentations (ptrend = 0.037), the presence of multi-vessel CAD (ptrend = 0.004), and modified Gensini scores (ptrend = 0.009). Similar dose-response relations of the aggregated score to leukocyte 8-OHdG and plasma ROS were also identified. Our data suggested reductions in both TL and mtDNA-CN as independent risk factors for CAD. The combination of TL and mtDNA-CN might jointly contribute to CAD risk, CAD severity, and oxidative stress. [Display omitted] •Lower leukocyte telomere length (TL) and mitochondrial DNA copy number (mtDNA-CN) independently increased coronary artery disease (CAD) risk.•The aggregated score of TL and mtDNA-CN may better predict CAD risk and severity.•The aggregated score may inversely correlate with markers of oxidative stress.